The Process of Dispute Resolution with Mediation in The Land Office of Batu City - Sherin Adriani; Salsabila, Firdina Nur Alfida Putri; Dwi Ratna Indri Hapsari (Universitas Muhammadiyah Malang, 2024)
The National Land Agency oversees government affairs in the land sector also has the authority to take administrative actions for resolving land disputes within its jurisdiction, playing a vital role in addressing land issues in Indonesia. According to the Regulation of the Minister of Agrarian Affairs also Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020, the BPN Kota Batu operates as a vertical agency under the National Land Agency also is directly accountable to the Minister through the Head of the Regional Office. This office serves as a mediator in local land disputes. The author conducts empirical legal research, including direct interviews with the Head of the Dispute Control also Handling Section at the BPN Kota Batu. Key issues examined involve the mediation process for resolving disputes also challenges encountered during mediation. Findings reveal that 1)the BPN Kota Batu adheres to proper procedures for mediation in line with applicable regulations, also 2)obstacles include 1)cooperation from the involved parties also 2)the mediator's capacity to facilitate dispute resolution effectively. Abstrak Badan Pertanahan Nasional mengawasi urusan pemerintahan di sektor pertanahan serta memiliki wewenang guna mengambil tindakan administratif dalam menyelesaikan sengketa tanah di wilayahnya, memainkan peran penting dalam menangani masalah pertanahan di Indonesia. Menurut Peraturan Menteri Agraria serta Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 21 Tahun 2020, Kantor Pertanahan Kota Batu beroperasi sebagai lembaga vertikal di bawah Badan Pertanahan Nasional serta langsung bertanggung jawab kepada Menteri melalui Kepala Kantor Wilayah. Kantor ini berfungsi sebagai mediator dalam sengketa tanah lokal. Penulis melakukan penelitian hukum empiris, termasuk wawancara langsung dengan Kepala Seksi Pengendalian serta Penanganan Sengketa di Kantor Pertanahan Kota Batu. Isu-isu kunci yang diteliti melibatkan proses mediasi guna menyelesaikan sengketa serta tantangan yang dihadapi selama mediasi. Temuan menunjukkan bahwa 1)Kantor Pertanahan Kota Batu mematuhi prosedur yang tepat guna mediasi sesuai dengan peraturan yang berlaku, serta 2)kendala yang dihadapi meliputi 1)kerja sama dari pihak-pihak yang terlibat serta 2)kapasitas mediator guna memfasilitasi penyelesaian sengketa secara efektif.